2009
DOI: 10.1111/j.1365-2222.2009.03314.x
|View full text |Cite
|
Sign up to set email alerts
|

CD4+CD25+ T cell depletion impairs tolerance induction in a murine model of asthma

Abstract: Both CD4(+)CD25(+) and CD4(+)CD25(-) T cells appear to be essential to tolerance induction. The relationship between both subsets and the mechanisms of their regulatory activity will have to be further analyzed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
38
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 44 publications
8
38
1
1
Order By: Relevance
“…Reduced proliferation could be related to the observed increase in Il-4r α mRNA expression, since soluble IL-4R may inhibit IL-4-mediated cell proliferation through neutralizing activity [43,44]. In accordance with our observations, nasal application of antigen has previously been described to lead to immunological tolerance characterized by induction of IgG1 [14,45], suppression of IgE, T-cell proliferation, cytokine secretion and allergic inflammation, when the same mice were concurrently sensitized [14,46]. Accordingly, in juvenile mice, intranasal OVA exposure induced OVA-specific IgG1 production, but restricted OVA-specific IgE and IgG1 production and allergic inflammation after immunization and airway challenge later in life (fig.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Reduced proliferation could be related to the observed increase in Il-4r α mRNA expression, since soluble IL-4R may inhibit IL-4-mediated cell proliferation through neutralizing activity [43,44]. In accordance with our observations, nasal application of antigen has previously been described to lead to immunological tolerance characterized by induction of IgG1 [14,45], suppression of IgE, T-cell proliferation, cytokine secretion and allergic inflammation, when the same mice were concurrently sensitized [14,46]. Accordingly, in juvenile mice, intranasal OVA exposure induced OVA-specific IgG1 production, but restricted OVA-specific IgE and IgG1 production and allergic inflammation after immunization and airway challenge later in life (fig.…”
Section: Discussionsupporting
confidence: 76%
“…First, we and others have shown that manipulation of the maternal immune response by allergen immunization during pregnancy reduces allergen-specific IgE production in offspring after immunization [10,11,12,13]. Second, mucosal delivery of allergen to naïve animals induces an active immune response characterized by suppression of allergen-specific IgE and T H 2-mediated inflammatory responses [14,15], but this has rarely been performed in neonates [16,17]. Induction of such mucosal tolerance simulates the processes occurring in healthy individuals, who do not develop adverse IgE-mediated reactions.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, a major cell type during the early phases of the response, are well known to play a central role in the host defense against Aspergillus (5,29,43,44,64) and were seen at all stages of the response, particularly at early stages prior to the engagement of the adaptive response. Levels of lung eosinophils, serum IgE, and IL-4 Expansion of the regulatory T cell population is important for limiting disease, because T reg cells ultimately aid in the clearance of fungi by limiting T H 1 inflammation (17) or dampening T H 2 hypersensitivity reactions (8,16). Exposure to A. fumigatus conidia or fungal glucan has been reported to induce regulatory responses via Toll-like receptor 2 (TLR2) and dectin-1 (19,46).…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the glucan-induced lung inflammation was characterized by a marked T H 1 response trending to a T H 2 immune response at the late stages of this in situ response (Young et al, 2001(Young et al, , 2006. T regs are increasingly believed to play a key role in controlling development of pulmonary inflammation (Boudousquié et al, 2009;D'Alessio et al, 2009;Tosiek et al, 2011). T regs modulate immune responses against external antigens, in part, by suppression of CD4 + and CD8 + T-cells (Belkaid et al, 2002;Suvas et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we attempted to investigate the role of IL-17/T H 17 cells and interaction between T regs and IL-17/T H 17 cells in a 1,3-β-glucan-induced inflammatory response using an established T reg -depleted mouse model (Boudousquié et al, 2009;Liu et al, 2011). As expected, the levels of Foxp3, a functional phenotype of T regs , decreased in T reg -depleted mice; these findings were confirmed by real-time PCR.…”
Section: Discussionmentioning
confidence: 99%